A time-based admission control mechanism for IEEE 802.11 ad Hoc networks - Costa, Luís Henrique M. K. (2006)
This paper presents a time-based admission control mechanism (TAC) for IEEE 802.11 ad hoc networks. The proposed mechanism was adapted to the QoS AODV routing protocol, which takes the quality of service requirements of the data flow into account in the route discovery process. TAC-AODV estimates the idle time of the physical medium based on the frames listened. The incoming traffic is admitted according to the offered load as well as the intra-flow interference, calculated based on the number of hops in the forwarding chain. TAC-AODV is compared to AAC-AODV, another admission control mechanism found in the literature, and the simulation results show that TAC-AODV is in average 12.5% better in terms of the packet delivery rate.